2017
DOI: 10.1051/0004-6361/201731879
|View full text |Cite
|
Sign up to set email alerts
|

What is the Milky Way outer halo made of?

Abstract: In a framework where galaxies form hierarchically, extended stellar haloes are predicted to be an ubiquitous feature around Milky Way-like galaxies and to consist mainly of the shredded stellar component of smaller galactic systems. The type of accreted stellar systems are expected to vary according to the specific accretion and merging history of a given galaxy, and so is the fraction of stars formed in-situ versus accreted. Analysis of the chemical properties of Milky Way halo stars out to large Galactocentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 140 publications
2
11
0
Order By: Relevance
“…We note that Milone et al (2020) did not find any significant differences in the multiple populations between star clusters associated with different progenitors (see also Saracino et al 2020). However, there has been a number of numerical and observational works attempting to describe the formation of globular clusters with multiple populations that are in very good agreement with some aspects of the intra-cluster Na enrichment scenario suggested in this work (see, e.g., Bekki 2006;Carretta et al 2010;Maxwell et al 2014;Battaglia et al 2017;Santistevan et al 2020).…”
Section: Analysis and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We note that Milone et al (2020) did not find any significant differences in the multiple populations between star clusters associated with different progenitors (see also Saracino et al 2020). However, there has been a number of numerical and observational works attempting to describe the formation of globular clusters with multiple populations that are in very good agreement with some aspects of the intra-cluster Na enrichment scenario suggested in this work (see, e.g., Bekki 2006;Carretta et al 2010;Maxwell et al 2014;Battaglia et al 2017;Santistevan et al 2020).…”
Section: Analysis and Discussionsupporting
confidence: 75%
“…It has been shown that the most Na-poor limit in dwarf galaxies is lower than the Na abundance of Milky Way field stars, with some exceptions (Colucci et al 2012;Ishigaki et al 2014;Battaglia et al 2017;Villanova et al 2019;Salgado et al 2019;Matsuno et al 2019;Aguado et al 2020). Therefore, first generation stars of globular clusters formed in accreted dwarf galaxies should mostly have Na abundances lower than their counterparts of globular clusters that formed in situ, which explains the range of 1G values seen in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…An external enrichment scenario is principally supported by the outer halo nature of HE 1327−2326 and similar metal-poor stars (Tissera et al 2014;Battaglia et al 2017). As such, they are likely accreted from some smaller now disrupted system, such as a primordial minihalo.…”
Section: Evidence For Aspherical Explosions From Rotationmentioning
confidence: 99%
“…An abundance study of the distant halo stars is of course possible (see e.g. Battaglia et al 2017) but is always limited to giant stars at fainter apparent magnitudes thus making such an endeavour much more laborious.…”
Section: Introductionmentioning
confidence: 99%